1998
DOI: 10.1108/09615539810226120
|View full text |Cite
|
Sign up to set email alerts
|

Forced convection of non‐Newtonian fluids in porous concentric annuli

Abstract: This study aims to numerically investigate the transient forced convection of non‐Newtonian fluid in the entrance region of porous concentric annuli. The hydrodynamic behavior of the flow is assumed to be steady and it is modeled using the non‐Darcian flow and the power law models. The transients in the thermal behaviors result from sudden changes in the boundary temperatures. The effects of different fluid flow and solid matrix parameters on the thermal behavior of the annular are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The heavy oil can be regarded as incompressible fluid and laminar flow in the capillary (Khashan and Al-Nimr, 2005;Alkam et al, 1998); and the tip effect and inertia force could be neglected for the long pipe and stable flow. Therefore, the viscous force equals the pressure differential from the inlet to the outlet.…”
Section: Test Of Heavy Oil Flowing Through Capillarymentioning
confidence: 99%
“…The heavy oil can be regarded as incompressible fluid and laminar flow in the capillary (Khashan and Al-Nimr, 2005;Alkam et al, 1998); and the tip effect and inertia force could be neglected for the long pipe and stable flow. Therefore, the viscous force equals the pressure differential from the inlet to the outlet.…”
Section: Test Of Heavy Oil Flowing Through Capillarymentioning
confidence: 99%
“…The presence of the porous medium magnifies the pressure drop which is significantly greater for dilatants fluids. The transient forced convection in a porous annular channel in the presence of a power-law fluid was investigated by Alkam et al [18]. It was shown that increasing permeability or decreasing the index n decreases the Nusselt number and the establishment length, whereas the opposite effect is observed when the Peclet number increases.…”
Section: Introductionmentioning
confidence: 98%
“…Chen and Hadim (1998) utilized the same flow model and the LTE assumption to numerically solve the hydrodynamically and thermally developing problem without boundary layer approximations. Alkam et al (1998) conducted a similar numerical study for the case of concentric annuli. Local thermal non-equilibrium (LTNE) conditions exist due to many obvious causes, such as the presence of distributed or concentrated heat sources in one phase or the presence of some agency which forces different fluid and solid boundary temperature conditions.…”
Section: Introductionmentioning
confidence: 99%